2019
DOI: 10.1007/s00345-019-02873-w
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy for bone oligometastatic disease in prostate cancer

Abstract: PurposeThere are sparse data describing outcomes of bone-only oligometastatic prostate cancer in comparison with lymph node disease treated with stereotactic body radiotherapy (SBRT). The primary aim of this study was to report progression-free survival (PFS) data for patients with bone-only disease. Influence of hormone sensitivity and androgen deprivation therapy use was also assessed.MethodsThis is a single-centre retrospective cohort study. Hormone-sensitive and castrate-resistant patients with oligometast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Grade 3 adverse events were observed in one patient (3%) [21]. Muldermans et al reported LC at 2 years of 82% after treating 69 patients with 81 metastases-88% received SFRS with a median dose of 16 Gy (range: [16][17][18][19][20][21][22][23][24] [37]. Seventy percent of patients were staged with choline PET/ CT.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Grade 3 adverse events were observed in one patient (3%) [21]. Muldermans et al reported LC at 2 years of 82% after treating 69 patients with 81 metastases-88% received SFRS with a median dose of 16 Gy (range: [16][17][18][19][20][21][22][23][24] [37]. Seventy percent of patients were staged with choline PET/ CT.…”
Section: Plos Onementioning
confidence: 99%
“…One-year local control (LC) rates reported after fractionated stereotactic body radiotherapy (fSBRT) for patients with oligometastatic prostate cancer vary from 93-100%. Besides, no grade �3 adverse events have been observed [18][19][20]. In this regard, single fraction radiosurgery (SFRS) is particularly attractive, since LC rates seem to be equally effective but treatment is delivered in a single session [21].…”
Section: Introductionmentioning
confidence: 99%
“…The cellular response of tumour cells to DNA damage treatment can be related to an underlying genetic background and can itself markedly alter gene expression to effect differential phenotypic behaviour ( 5 , 6 ). Crucially, RT is no longer restricted to use in the treatment of local disease but is becoming a viable therapeutic option for advanced disease, with clinical trials currently evaluating the potential use of stereotactic RT to treat oligometastatic CaP ( 7–9 ). The extended deployment of radiation as an intervention across the continuum of the clinical landscape accentuates the requirement to optimize this treatment modality.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular response of tumor cells to DNA-damage treatment can be related to an underlying genetic background and can itself markedly alter gene expression to effect differential phenotypic behaviour (Kumareswaran, Ludkovski et al, 2012, Taiakina, Dal Pra et al, 2014). Crucially, RT is no longer restricted to use in the treatment of local disease but is becoming a viable therapeutic option for advanced disease, with clinical trials currently evaluating the potential use of stereotactic RT to treat oligometastatic CaP (Muldermans, Romak et al, 2016, Ost, Jereczek-Fossa et al, 2016, Patel, Chaw et al, 2019). The extended deployment of radiation as an intervention across the continuum of the clinical landscape accentuates the requirement to optimize this treatment modality.…”
Section: Introductionmentioning
confidence: 99%